Objects Influence the Shape of Remembered Views: Examining Global and Local Aspects of Boundary Extension. (August 2014) - Dickinson, Christopher A; LaCombe, Daniel C
Boundary extension is a constructive memory error for views of scenes in which views tend to be remembered as more spatially expansive than they appeared. In seven experiments we examined whether local differences in boundary extension within views might exist by presenting participants with overhead views of single, elongated objects or object pairs on textured ground surfaces in which objects were oriented either vertically or horizontally. Memory for views' spatial expanse was tested with either a view-recognition test or a border-adjustment test in which participants could adjust the spatial expanse of a test view using the computer's mouse. The border-adjustment test was used to assess local boundary extension (primarily); the view-recognition test was used to assess participants' memories for the overall spatial expanse of views (ie global boundary extension). Across experiments, in the border-adjustment tests specifically, participants showed more spatial expanse along the object's longer axis, in some cases restricting the view along the object's shorter axis. In addition, the recognition-test data revealed greater boundary extension for views with vertically oriented objects than for views with horizontally oriented objects. Taken together, the results suggest that objects in scene views can affect both local and global aspects of memory for spatial expanse of scene views.